Characteristics of lightning flashes generating sprites above storms - Soula Serge; van der Velde Oscar; Montanya Joan; Fullekrug Martin; Mezentsev Andrew; Mlynarczyk Janusz (E3S Web of Conferences, 2016)
Sprites are Transient Luminous Events (TLEs) that can extend vertically from 40 to 90 km and horizontally over several tens of km to form clusters of individual or multiple column or/and carrot-shaped luminous elements. They can even extend over more than 100 km in the form of sequential luminous emissions that are called “dancing sprites”. Their optical detection and other parameters describing the storm and the lightning activity associated allow us to understand the conditions of their production and their links with the lightning activity. Our observations confirm some characteristics of the sprites and put forward others: (i) the sprites are essentially produced above the stratiform region of the Mesoscale Convective Systems after positive cloud-to-ground lightning flashes that produce large Charge Moment Change (CMC), with a shorter delay if the impulsive CMC (iCMC) is larger. (ii) The dancing sprites reflect the timing and the location of the successive lightning strokes that generate them. (iii) The sprite elements can be shifted from the stroke location when their delay is large. (iv) Bright sprites produce current signatures in ELF radiation a few milliseconds (<5 ms) after the positive strokes that generate them.